Toxicity of methoprene as assessed by the use of a model microorganism - Monteiro, J. P. (2005)
Methoprene is an insect juvenile growth hormone mimic, commonly used as a pesticide. Although widely used for the control of several pests, toxic effects on organisms of different phyla have been reported. These events triggered studies to clarify the mechanisms of toxicity of this insecticide putatively involved in ecological issues. Here we show the effect of methoprene on the normal cell growth and viability of a strain of the thermophilic eubacterium Bacillus stearothermophilus, previously used as a model for toxicological evaluation of other environment pollutants. Respiration studies were also carried out attempting to identify a putative target for the cytotoxic action of methoprene. Cell growth was affected and a decrease of the number of viable cells was observed as a result of the addition of methoprene to the growth medium, an effect reverted by the presence of Ca2+. Methoprene also inhibited the redox flow of B. stearothermophilus protoplasts before the cytochrome oxidase segment, an effect further studied by individually assessing the enzymatic activities of the respiratory complexes. This study suggests that methoprene membrane interaction and perturbation of cell bioenergetics may underlie the mechanism of toxicity of this compound in non-target organisms.